Legacy appliance integration in home management energy system for energy saving. (9th January 2023) - Sabri, Anwar AbdulJabbar; Sheikh, Usman Ullah; Said, Dalila Mat
This paper presents legacy appliance profile integration of home management energy system for energy saving. Legacy appliances are associated with the poor determination of power and electricity profile, and has difficulties in integrating into smart home energy system. Hence, this work focuses on implementation of legacy appliances profile with home energy management system (HEMS) and monitors different legacy appliances based on their energy consumption. The legacy appliance profile is measured and profiled with the help of smart socket. The model is designed and implemented on circuits Tinker card software with Arduino (UNO ATmega328P chip) controller. Then, the legacy appliances profile is integrated with HEMS and monitored their power demands. An energy saving reduction of 34% is achieved using the proposed model. A measured power consumption of 159 kW per month is obtained using the proposed HEMS compared to 243 kW without HEMS.